Analisis Pengaruh Rasio Likuiditas, Solvabilitas, Aktivitas, dan Profitabilitas Terhadap Return Saham (Studi Empiris Pada Perusahaan Sektor Infrastruktur, Utilitas dan Transportasi yang Terdaftar di BEI Periode 2014-2017 - Diah Wahyuning Tyas; Ronny Malavia Mardani; Budi Wahono (E-JRM : Elektronik Jurnal Riset Manajemen, 2018)
Abstract               The purpose of this research is to how influence analysis Current Ratio (CR), Debt to Equity Ratio (DER), Total Asset Turnover (TATO) and Return on Assets (ROA) to Stock returns.              The population in this research is sector companies in infrastructure, utilities and transportation listed on the Indonesia Stock Exchange (IDX) for the period 2014-2017. Sample selection using purposive sampling method. The method used is multiple linear regression analysis with hypothesis testing using t test.              The results showed that the variable Current Ratio (CR) had a negative and insignificant effect on stock returns. Debt to Equity Ratio (DER) has a positive and insignificant effect on stock returns. Total Asset Turnover (TATO) has a negative and insignificant effect on stock returns. And Return on Assets (ROA) has a positive and significant effect on stock returns. Keywords: Current Ratio (CR), Debt to Equity Ratio (DER), Total Asset Turnover (TATO), Return On Assets (ROA) and stock returns.